CCAFS Guide to Dissemination of Research Outputs - Ramírez, Margarita M.; Pantoja, Ana Maria; Epp, Marissa van; Abreu, David; Tobon, Hector (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This is an info graphic for all of MARLO users.